THE SYNTHESIS, CHARACTERIZATION, DFT-OPTIMIZATION, BIOLOGICAL ASSAYS, AND HEAVY METAL STUDIES OF A NEW TETRA DENTATE DERIVATIVE LIGAND AND ITS COMPLEXES - Azeez, Kwestan Namiq Azeez; Eman Ibraheem (Science Journal of University of Zakho, 2025)
A new tetra dentate derivative ligand [(E)-N-((E)-(2-(((Z)-1-hydroxybutylidene) amino) phenyl) (isopropylimino) methyl) butyrohydrazonic acid] [N3O] type has been prepared from the condensation process of equimolar 2-aminobenzohydrazide, isopropyl amine and followed by another addition of butyric acid. Spectroscopic techniques as FT-IR, UV-visible, Mass spectrum, 1H,13C-NMR, T.L.C., Melting point, Conductivity measurements, Magnetic moment, DFT-optimization studies and other methods have been used to characterize the ligand and its new complexes with the general formula [L(M2)Cl3.H2O] (where M= NiII, CoII, CuII, MnII, CdII, and ZnII). Studying biological activity for the ligand and its complexes against two gram-positive and two gram-negative bacteria . The formed compounds were evaluated for antibacterial activity against two gram-positive and two gram-negative bacteria which are Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Pseudomonas aeruginosa. The developed ligand and its metal complexes performed well versus both kinds of bacteria Scheme 1